How aspects of similar datasets can impact distributional models - Gomes, Isabella Maria Alonso; Roman, Norton Trevisan (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2022: Anais do XIX Encontro Nacional de Inteligência Artificial e ComputacionalDO - 10.5753/eniac.2022.227085, 2022)
Distributional models have become popular due to the abstractions that allowed their immediate use, with good results and little implementation effort when compared to precursor models. Given their presumed high level of generalization it would be expected that good and similar results would be found in data sets sharing the same nature and purpose. However, this is not always the case. In this work, we present the results of the application of BERTimbau in two related data sets, built for the task of Semantic Similarity identification, with the goal of detecting redundancy in text. Results showed that there are considerable differences in accuracy between the data sets. We explore aspects of the data sets that could explain why accuracy results are different across them.